A study on the influence of corporate social responsibility dimensions on employee engagement in the banking industry - Chen, Yen Teng; Hew, Kah Mun; Prem Kumar, Munusamy; Siak, Wen Jing (2024)
In the competitive business environment, it is particularly critical to understand the importance of corporate social responsibility because employee engagement has a direct impact on the organizational performance and development. Employees who are engaged in corporate social responsibility not only empower them to leverage corporate resources to do good for the world, but also boost employee morale in the workplace and lead to greater productivity. Therefore, it has become an organization’s responsibility to establish a culture and environment that enhances employee’s work engagement. In the banking industry, employees who contribute to a company's bottom line are much happier, more satisfied, and more productive. Although there has been much research on employee engagement, relatively little research has been conducted in the banking industry, mostly focusing on areas such as telecommunication, hospitality, and healthcare industries. Therefore, this study chose to use quantitative research to explore corporate social responsibility on employee engagement in the banking industry. In order to collect data, 150 questionnaires were distributed to employees of the banking industry in Selangor, Malaysia through Google Forms in order to obtain their feedback. After collecting the questionnaire, the data was analyzed using Statistical Package for Social Science (SPSS). Cronbach’s alpha reliability test and multiple regression analysis were used in the study to assess the relationship between the dependent variable (employee engagement) and the independent variables (economic responsibility, legal responsibility, ethical responsibility, philanthropic responsibility). The result showed that ethical responsibility and philanthropic responsibility had a significant correlation to employee engagement; economic responsibility and legal responsibility had an insignificant correlation to employee engagement.